The peril and promise of Christian liberty: Richard Hooker, the Puritans, and protestant political theology - Littlejohn, W. Bradford (Emory University Studies in Law and Religion Ser, 2017)
Intro -- Title Page -- Copyright -- Contents -- Acknowledgments -- Abbreviations and Notes on Citations -- A Note on Spelling and Punctuation -- 1. "Different Kings and Different Laws": Christian Liberty and the Conflict of Loyalties since the Reformation -- 2. Freedom for the Neighbor: Christian Liberty and the Demand for Edification -- 3. "Exact Precise Severity": The Puritan Challenge to Prince and Conscience -- 4. Richard Hooker and the Freedom of a "Politic Society": Between Legalism and Libertinism -- 5. Harmonized Loyalties: Conscience, Reason, and Corporate Moral Agency -- 6. The Soul of a Christian Commonwealth: Politics in Submission to the Word -- 7. "The Truth Will Set You Free": The Peril and Promise of Christian Liberty -- Bibliography -- Index